Legal Analysis of Legal Consequences for Notaries for Violating the Honorarium Provisions in Making Deeds - Dwi Jayanto, Ilham (Jurnal Konstatering, 2024)
This study aims to determine the determination of the Notary's honorarium in making a Deed and to determine the legal consequences for Notaries who violate the honorarium provisions in making a Deed. The research approach method used in this thesis is the normative legal research method. The approach used in this study is the Legislation (statute approach). The type of data used in this study is primary data which includes the 1945 Constitution; Civil Code; Law Number 30 of 2004 concerning amendments to Law Number 2 of 2014 concerning the Position of Notary; Notary Code of Ethics. The data analysis method used is secondary data that has been obtained, analyzed descriptively qualitatively. The results of the study show that the determination of the notary's honorarium in making a Deed is based on the Economic Value and/or Sociological Value of each Deed made. The Economic Value of each deed has been regulated in Article 36 paragraph (3) of the UUJN, and the UUJN regulates the maximum limit of honorarium and the Code of Ethics regulates the minimum limit of honorarium, and in Article 37 of the UUJN, Notaries are required to provide free legal services to people who are unable to afford it without charging an honorarium. Violations committed by Notaries due to charging an honorarium below the provisions stipulated in the Code of Ethics, then the sanctions that will be given based on the Code of Ethics are: a) Reprimand; b) Warning; c) Schorsing; (temporary dismissal) from membership of the Association; d) Onzetting (dismissal) from membership of the Association; e) Dishonorable dismissal from membership of the Association. Sanctions for violating the provisions of the honorarium according to the UUJN, For the first sanction is a verbal warning. When a verbal warning is not complied with by a Notary, the next tiered sanction that must be received by the Notary is a written warning.